FACTORS PROMOTING THE TEACHER TRAINING AND PROFESSIONAL TRAINING BASED ON A HIERARCHICAL APPROACH IN THE ENVIRONMENT OF DIGITAL EDUCATION - Ergashev Nuriddin Gayratovich (European Science Publishing, 2025)
In the context of an information society, the environment of continuing education is rapidly changing due to new realities and modern educational needs. One of the most popular areas of innovative activity in the current period is the organization of training in the technical economy of higher education using electronic information educational environment tools in the training of students based on a hierarchical approach, which in turn creates opportunities for the transition to the principle of continuing education. It should be noted that in modern developed countries and in our country, a number of terms are used in relation to distance learning technology: distance learning, distance learning, electronic learning, distance learning.
Keywords: Pedagogical process, digital technology, technical systems, hierarchical approach, teaching, scientific and methodological system, model, etc.